Selection of 7-10 Years Old Children of Different Types of Constitution in Sport Swimming, Taking Into Account Their Psychological and Physiological Features - Vladimir Davydov; Anna Mankevich; Olga Morozova (Lesya Ukrainka Volyn National University, 2017)
The article revealed the need to consider the psychophysiological parameters of the central nervous system of the children of schoolchildren in the selection and orientation of the sport swimming. The interrelation of features such as the schoolchild constitution and the activity of his central nervous system has been revealed. Presented conducted an extensive research of boys 7-10 years old and based on the analysis of selected types of the most successful, the algorithm is composed of sports selection procedure, revealing the specificity and individuality of each student, which increases the effectiveness of achieving high results in the future.